Optimasi Peran Negara terhadap Tindakan Penyalagunaan Kekuasaan dalam Kondisi Darurat Covid-19 - Merta, M. Martindo (Jurnal Kepastian Hukum dan Keadilan, 2021)
Law Number 3 of 1971 concerning the Eradication of Criminal Acts of Corruption is no longer in accordance with the development of legal needs in society, therefore it needs to be replaced with a new Law on the Eradication of Criminal Acts of Corruption so that it is expected to be more effective in preventing and eradicating criminal acts of corruption. On the basis of such considerations, it is necessary to establish a new Law on the Eradication of Corruption Crimes; The legal basis for this law is: Article 5 paragraph (1) and Article 20 paragraph (1) of the 1945 Constitution; and Decree of the People's Consultative Assembly of the Republic of Indonesia Number XI/MPR/1998 concerning State Organizers that are Clean and Free of Corruption, Collusion and Nepotism. This Law regulates: Corruption Crimes; Other Crimes Related to Corruption; Investigation, Prosecution, and Examination in Court Sessions; And Community Participation. This Law also mandates the establishment of a Corruption Eradication Commission which will be regulated in a separate Law within a period of no later than 2 (two) years from the promulgation of this Law. The membership of the Corruption Eradication Commission consists of elements of the Government and elements of the communityKeywords: Corruption Crime, Investigation, Government